2008
DOI: 10.1039/b804842h
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the voltammetric reduction of methylviologen at gold and carbon based electrode materials. Evidence for a surface bound adsorption mechanism leading to electrode ‘protection’ using multi-walled carbon nanotubes

Abstract: Cyclic voltammetry was recorded in an aqueous solution of 1,1'-dimethyl-4,4' bipyridinium dichloride (“methylviologen” or “paraquat”) at a variety of electrode materials namely gold, boron doped diamond (BDD), edge (eppg) and basal plane (bppg) pyrolytic graphite electrode. Previous mechanisms reported in the literature to describe the observed voltammetry are critically assessed and an alternative mechanistic interpretation is presented involving evidence for surface adsorption of intermediate species in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
2
13
0
1
Order By: Relevance
“…Moreover, in Figure 2 A the GC electrode also exhibited two reversible process and with the highest current signal. However, previous literature results have shown that strong adsorption occurs during repetitive cycles, which fouls the surface of the electrode and compromises the analysis 21. In addition, the background current obtained using the GC electrode was higher, indicating that this material has a poor limit of detection.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, in Figure 2 A the GC electrode also exhibited two reversible process and with the highest current signal. However, previous literature results have shown that strong adsorption occurs during repetitive cycles, which fouls the surface of the electrode and compromises the analysis 21. In addition, the background current obtained using the GC electrode was higher, indicating that this material has a poor limit of detection.…”
Section: Resultsmentioning
confidence: 92%
“…The reversibility of redox process to PQ in the BDD electrode was confirmed by peak potential separation for both process equal to 65 mV (value closed to theoretical Nernst prevision (59.16/n) mV) and the ratios of anodic and cathodic peak current ( I p,a / I p,c ) closed to 1. The first couple, at −0.66 V is attributed to Equation 1 21 …”
Section: Resultsmentioning
confidence: 99%
“…These results agree well with previously published data in several references. [2,12,15] As illustrated in Figure 2 a, these waves (peaks) are due to electron-transfer processes for the reduction reactions from MV 2 + to MV + and further from MV + to MV 0 as well as for corresponding oxidation reactions from MV 0 to MV + and further from MV + to MV 2 + . Although it is known that the reduction reaction from MV + to MV 0 involves both diffusion and adsorption processes, the current scales and the shape of these waves do not alter much on this macroscopic diamond electrode when its surface termination is changed from HT (black curve in Figure 2 a) to OT (green curve in Figure 2 a).…”
Section: Introductionmentioning
confidence: 94%
“…It has been studied on a variety of macroscopic electrodes as a redox mediator, as a herbicide or with respect to its electrochromic characteristics. [10][11][12][13][14] The macroscopic electrodes include metal electrodes and carbon-related materials (e.g., glassy carbon and boron-doped diamond). [10][11][12][13][14] Importantly, the reduction and oxidation of MV + to MV 0 is reported to involve diffusion as well as the adsorption of the neutral species on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…Nanogold or single or multi-walled carbon nanotube modified electrodes are two common electrodes widely used for these purposes [4][5][6][7]. Recently, the nanomaterial-composite modified electrodes have been claimed to exhibit much higher sensitivity in comparison to only nanomaterials modified electrodes [8,9].…”
Section: Introductionmentioning
confidence: 99%